KOMPETENSI PENGAJARAN GURU BAHASA MELAYU PRASEKOLAH PENDIDIKAN KHAS DARI PERSPEKTIF KERANGKA STANDARD BAHASA MELAYU (KSBM) (Proceedings of International Conference on Special Education, 2019)
The study aims to find the competence of Malay language teaching proficiency in special education preschool through the evaluation of the management and practice of special education preschool teachers from the perspective of the Standard Malay Language Framework (KSBM). The study involved special education preschool teachers around the Klang valley, following the Workshop on Speaking Arts in teaching and facilitating (PdPC) special education preschool organized by the Department of Malay Civilization and Culture, IPG Malay Language Campus. The research methodology involved a set of questionnaire consisting of 25 items. The five constructs of the teaching of Malay language teachers in special education preschool were assessed, namely the competence of teaching listening skills, the teaching competence of speaking skills, the competence of teaching reading skills, the competence of teaching writing skills, and the teaching competence of language arts. This quantitative survey study involves KSBM's perspective of 50 special education pre-school teachers. The data obtained were analyzed in descriptive stastistic form, involving analysis in frequency, average score and percentage. The findings of the study find the competence of Malay language teaching practitioners in special education preparations through the assessment of the practice of teaching Malay language teachers in special education preschool from KSBM's perspective, on most items are at a moderate and satisfactory level. All five constructs of teaching competence in the teaching of Malay language teachers in special education preschools, in terms of competence teaching listening skills, speaking skills teaching, reading skills teaching, writing skills teaching, and language teaching competency assessed as 'good' achievement. The views of special education preschool teachers on the strength of Malay language teaching competence in special education preschools in PdPC, are from the aspect of KSBM teaching skill competence. While the KSBM aspect of language teaching competence, it reached the lowest level. In this regard, the need for special education teachers of pre-school Malay language to continue to be exposed and the PdPc training underlying KSBM in the 21st century education era, is a necessity. In addition, to achieve the educational goal of developing the spirit and soul of the disability of special education preschools, fulfilling the aspirations of national education and the realization of the national education policy, as well as for a continuation of global education challenge at the level of pre-school education.